Clinical and genetic features of four patients with Pearson syndrome: An observational study. Issue 5 (4th February 2022) - Son, Ji Soo; Seo, Go Hun; Kim, Yoon-Myung; Kim, Gu-Hwan; Jin, Hee Kyung; Bae, Jae-sung; Im, Ho Joon; Yoo, Han-Wook; Lee, Beom Hee
Abstract : Abstract: Pearson syndrome (PS) is a multisystem mitochondrial cytopathy arising from deletions in mitochondrial DNA. Pearson syndrome is a sporadic disease that affects the hematopoietic system, pancreas, eyes, liver, and heart and the prognosis is poor. Causes of morbidity include metabolic crisis, bone marrow dysfunction, sepsis, and liver failure in early infancy or childhood. Early diagnosis may minimize complications, but suspicion of the disease is difficult and only mitochondrial DNA gene testing can identify mutations. There is no specific treatment for PS, which remains supportive care according to symptoms; however, hematopoietic stem cell transplantation may be considered in cases of bone marrow failure. We herein describe the clinical and genetic characteristics of four patients with PS. One patient presented with hypoglycemia, two developed pancytopenia, and the final patient had hypoglycemia and acute hepatitis as the primary manifestation. All patients had lactic acidosis. Additionally, all patients showed a variety of clinical features including coagulation disorder, pancreatic, adrenal, and renal tubular insufficiencies. Two patients with pancytopenia died in their early childhood. Our experience expands the phenotypic spectrum associated with PS and its clinical understanding.